Data and its Acuities (International Journal of Psychosocial Rehabilitation, 2020)
Revolution in data provides a space to classify traditional data and big data. Opportunities with mounting data have drastically changed in today’s business environment; hence, business analytics undoubtedly has become one of the most sought-after professions in the contemporary business environment. In fact, business analytics is going to be the next domain that will drive careers in the next few years. Data scientists are getting a good understanding of the climate crisis to resolve solutions for the problems of the natural resources. In this paper, the author discussed the classification between traditional data and big data, opportunities, and challenges. Primary data shall be collected from industry and academic professionals to study the opportunities and challenges of bigBig Data data for better decisions in any environment.